Improving efficiency in public financial management a study on the adoption of the Unified Account Code Structure (UACS) in select national government agencies - Quilinguing, Agnes Kristine Aranza; Alampay, Erwin Gaspar A. (Quezon City National College of Public Administration and Governance, University of the Philippines Diliman, 2019)
The Philippine government has been implementing the Unified Account Code Strucure (UACS) as an integral component of the Public Financial Management (PFM) Reform Program since 2014. It is meant to simplify, improve, and harmonize government's financial management process and information systems. Through UACS, oversight and implementing agencies share a common set of financial data and information , from budgeting and cash management to accounting and audit. The use of codes help simplify and consolidate formats for financial reports; facilitates timely and accurate reporting of actual receipts and expenditures agaisnt programmed revenues and expenditures; and enables comparison of disbursements for programs, projects, and activities with their approved appropriations.
In this context, the study looked at the adoption of the UACS reform in national government agencies using the Technology Acceptance Model (TAM). Through the use of a survey of budget officers, accountants, cashiers from the top ten spending agencies of government, this study described UACS's perceived usefulness and ease of use towards agencies' actual system use. UACS's usefulness was determined in terms of UACS application to budget cycle: budget preparation, legislation, execution, and accoutnability. UACS's ease of use, on the other hand, was ascertained through a comparison between UACS and the old system.
Survey result showed that all national government agencies have already adopted and continue to use the UACS. Through various financial management information systems, spending agencies all use UACS in all phases of the budget cycle. Since the financial management information systems has been updated to comply with UACS requirements. PFM personnel, including budget officers, accountants, and cashiers found it easy to apply UACS in their work. The study found that adoption of UACS has been sustained despite a change in administration. Training on its use has lagged largely because newer employees are no longer transitioning from an old system to a new one. While majority agreed that it is useful, most were neutral when comparing it with the older system in terms of ease of use. Accountants and budget officers had more positive views about the system being easier to use. This was consistent with accountants and budget officers finding that the UACS is useful in streamlining the reporting requirements which was not the case for cashiers
Thesis(Master of Public Administration)--University of the Philippines Diliman
Keywords: Finance, Public -- Philippines; Accounting -- Standards -- Philippines; Fiscal policy -- Philippines